El impacto laboral de la nueva organización de la empresa: el ejemplo de la cesión ilegal de trabajadores - Cuenca Alarcón, Miguel (Cuadernos de Relaciones Laborales, 2008)
The great impact of the new forms of organization on the labour relations has not provoked a general mobilization of the Spanish labor law in order to guarantee balanced solutions between the different concurrent interests. This paper gives a panoramic view of Spanish labour law, with special reference to the regulation of illegal contracts for placing workers at the disposal of another company.
Keywords: Outsourcing; Transfer of undertaking; Illegal contract for placing workers at the disposal of another company